2015
DOI: 10.1186/s40795-015-0029-3
|View full text |Cite
|
Sign up to set email alerts
|

A healthy eating index to measure diet quality in pregnant women in Singapore: a cross-sectional study

Abstract: Background: There are limited tools to assess diet quality in pregnant women in an Asian population. A healthy eating index for pregnant women in Singapore (HEI-SGP) was developed and its association with maternal characteristics examined. Methods: The HEI-SGP was adapted from the Healthy Eating Indices (HEI) and Alternate Healthy Eating Index for Pregnancy (AHEI-P) and modified accordingly to recommendations from the Singapore dietary guidelines for pregnant women. It included eight components to reflect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 33 publications
4
49
1
2
Order By: Relevance
“…Our external validation against the mAHEI(46), which has been used previously to assess 319 diet quality in pregnant women (55), found that mAHEI score was associated with greater 320 adherence to the plant-based and health-conscious diet patterns and lower adherence to the 321 Western diet, which confirms alignment of our dietary patterns with external methods for 322 assessing diet quality. 323…”
Section: Condiments 219supporting
confidence: 55%
See 1 more Smart Citation
“…Our external validation against the mAHEI(46), which has been used previously to assess 319 diet quality in pregnant women (55), found that mAHEI score was associated with greater 320 adherence to the plant-based and health-conscious diet patterns and lower adherence to the 321 Western diet, which confirms alignment of our dietary patterns with external methods for 322 assessing diet quality. 323…”
Section: Condiments 219supporting
confidence: 55%
“…To 48 overcome the limitations of single-nutrient or single-food studies, the empirical derivation of 49 dietary patterns Ñ defined as Òthe quantities, proportions, variety or combinations of different 50 foods and beverages in diets, and the frequency with which they are habitually consumedÓ (13), 51 has been proposed as a method to characterize diet that more accurately reflects how we 52 consume foods or nutrients, and these patterns can be assessed for their associations with health 53 and disease. (14-18) 54 Canada is an ethnically diverse nation (19) which introduces challenges for healthcare 55 providers tasked with providing evidence-based dietary advice, because much of what we know 56 about diet and disease is rooted in studies of white European populations. Dietary choice is 57 closely tied to ethnicity (e.g., foods, cooking methods, and eating habits) (20) and the degree to 58 which an individual or community consumes ethnically-traditional foods can be influenced by 59 immigration and residency in a host country.…”
mentioning
confidence: 99%
“…), and the results may not be applicable to other populations of pregnant women (18). The intake of sweetened beverages was accounted for in the DASH diet (21) but less emphasized in other diet quality indexes (13,15,16,19,30). Earlier studies have shown that the intake of sweetened beverages during pregnancy is associated with an increased risk of preterm birth (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…The HEI-SGP has been validated to examine diet quality of pregnant women in Singapore (30) and, to date, has been associated with health outcomes such as maternal retinal microvasculature abnormalities (31) and gestational diabetes (in preparation). In brief, the HEI-SGP has 11 components with a maximum possible raw score of 90.…”
Section: Diet Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation